Pendapat Ulama Kota Banjarmasin Terhadap Jual Beli Emas Dengan Sistem Tabungan Emas Melalui Aplikasi Dana - Nurhalisa; Rabiatul Adawiyah (Sharia Journal and Education Center Publishing, 2024)
Advances in technology and information systems in the field of financial technology provide many conveniences for society. One of them is the convenience of online gold buying and selling services through applications, such as fund applications which are different from offline transactions. This application uses digital services designed to make it easier for users to save gold practically. However, this raises questions regarding the legal position of buying and selling gold online. Based on these problems, the author wants to know the legal basis and reasons underlying the opinions of ulama in Banjarmasin City regarding buying and selling gold using the gold savings system through the Dana Application. This research uses empirical legal research methods with a sociological approach. The location of this research is Banjarmasin City. As for the findings from the research, first, there are two variations of opinion from six Banjarmasin City ulama, namely: 1. Permissible, in this case there are two criteria, namely; a. allow as long as they are harmonious and the conditions are met, b. possible but best avoided. 2. Not allowed. Second, the legal arguments used by Banjarmasin City ulama are, 1. Permissible with two criteria, a. allows it as long as it is harmonious and the conditions are met using the QS arguments. al-Baqarah/2:275, QS. al-Baqarah/2: 282, and QS. an-Nisa/4:29. b. It is possible but should be avoided based on the QS argument. al-Baqarah/2:188. 2. It is not permissible to use the hadith narrated by at-Tirmidhi hadith number 2518 and an-Nasa'i hadith number 5711, the hadith narrated in Sahih Muslim Number 1513 from Abu Hurairah RA and the hadith of the Prophet Muslim History, Abu Daud, Tirmizi, Nasa' I and Ibn Majah from 'Ubadah bin Shamit